How can human-centered design build a story-based video intervention that addresses vaccine hesitancy and bolsters vaccine confidence in the Philippines?: a mixed method protocol for project SALUBONG - Reñosa, Mark Donald; Wachinger, Jonas; Bärnighausen, Kate; Aligato, Mila F.; Landicho-Guevarra, Jhoys; Endoma, Vivienne; Landicho, Jeniffer; Bravo, Thea Andrea; Demonteverde, Maria Paz; Guevarra, Jerric Rhazel; Iii, Nicanor de Claro; Inobaya, Marianette; et al. (BMJ open, 2021)
Introduction Since the onset of a dengue vaccine controversy in late 2017, vaccine confidence has plummeted in the Philippines, leading to measles and polio outbreaks in early 2019. This protocol outlines a human-centered design (HCD) approach to co-create and test an intervention that addresses vaccine hesitancy (VH) via narrative and empathy with and among families and healthcare workers. - Methods and analysis ‘Salubong’ is a Filipino term that means to welcome someone back into one’s life, reinforcing notions of family ties and friendships. We apply this sentiment to vaccines. Following the phases of HCD, guided by a theoretical framework, and drawing from locally held understandings of faith and acceptance, we will conduct in-depth interviews (IDIs) and focus group discussions (FGDs) in rural and urban Filipino communities that witnessed dramatic increases in measles cases in recent years. During qualitative engagements with caretakers, providers, and policymakers, we will collect narratives about family and community perceptions of childhood vaccinations, public health systems and opportunities to restore faith. IDIs and FGDs will continuously inform the development of (and delivery mechanisms for) story-based interventions. Once developed, we will test our co-created interventions among 800 caretakers and administer a VH questionnaire prior to and immediately following the intervention encounter. We will use the feedback gained through the survey and Kano-style questionnaires to further refine the intervention. Considering the data collection challenges posed by the ongoing COVID-19 pandemic, we have developed workarounds to conduct data collection primarily online. We will use systematic online debriefings to facilitate comprehensive participation of the full research team. - Ethics and dissemination Ethical approval has been granted by the Institutional Review Board of the Research Institute for Tropical Medicine (number 2019-44) and Ethical Commission of Heidelberg University, Faculty of Medicine (S-833/2019). Study findings will be disseminated in scientific conferences and published in peer-reviewed journals.